Comparative Evaluation of Accuracy of Different Apex Locators: Propex IQ, Raypex 6, Root ZX, and Apex ID with CBCT and Periapical Radiograph—In Vitro Study - Okba Mahmoud; Mawada Hassan Awad Abdelmagied; Ahmad Hisham Dandashi; Bakr Nssaief Jasim; Hussam Alddin Tawfik Kayali; Saaid Al Shehadat (International Journal of Dentistry)
Objectives. This study aimed to validate the accuracy of working length (WL) measurements obtained with the newly introduced Propex IQ apex locator and to compare it with the latest generations of other electronic apex locators, CBCT, and conventional periapical radiographs by using the actual WL measurements obtained by using an endodontics microscope as a reference. Materials and Methods. Thirty-five extracted single-rooted human mandibular first premolars with curvatures from 10° to 20° were selected according to the inclusion and exclusion criteria and cut at the cementoenamel junction to achieve a standard reference point for WL determination. The actual WL was obtained by inserting a size-15 k-file in the root canal until the tip of the file was visible under an endodontic microscope. The definitive WL was measured using Propex IQ (Dentsply Sirona), Raypex 6 (VDW Dental), Root ZX (Morita), and Apex ID (Kerr Dental). In addition, radiographic WL was obtained using periapical radiographs and CBCT. One-way ANOVA was used for comparisons of the WL values, with a p value < 0.05. The percentage of success of each method for determination of the definitive WL was assessed using cross-tabulation and chi-square tests. Results. CBCT radiographs and Propex IQ apex locator yielded the most accurate WL measurements in comparison with the actual WL measurements (p<0.05). Raypex 6, Root ZX, and Apex ID yielded more accurate WL measurements than conventional periapical radiographs (p<0.05). Periapical radiographs yielded the least accurate WL measurements in comparison with the actual WL values (p<0.05). Conclusions. Within the limitations of this study, the Propex IQ apex locator showed higher accuracy than Raypex 6, Root ZX, and Apex ID for WL determination in the root canal. Nevertheless, CBCT radiographs yielded the maximum accuracy for WL measurements.